ANALISIS BUKU TEKS MATA PELAJARAN SENI BUDAYA PADA KURIKULUM TINGKAT SATUAN PENDIDIKAN DI KOTA SEMARANG - Aesijah, Siti (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
The interesting study is about appropriateness among content in textbook art material in SMPas source in KTSP curriculum, with teachers, students, and school condition. This researchuses qualitative approach. Data collection techniques are observation, interview, anddocumentation. Analyzing data done by using descriptive-qualitative analysis. Techniques ofchecking relevance data use cross-recheck validity. Based on the research result, writtentextbook, which distributed in schools have fulfilled material scope appropriate withcompetence expected in the curriculum, but the utilization was not in maximum. There arefew textbooks that using utilization guidance organized by Ã¢â‚¬Å“YudhistiraÃ¢â‚¬Â publisher but theexplanation of content is less systematically. Ã¢â‚¬Å“ErlanggaÃ¢â‚¬Â publisher have explained materialsystematically but it is not enough to simulate studentsÃ¢â‚¬â„¢ thought, however Ã¢â‚¬Å“Tiga SerangkaiÃ¢â‚¬Âpublisher have presented music material completely but it is presented not interestingly. Eachpublisher has their own superiority but they also have drawback. Therefore, teachers canexploit the superiority of each publisher but cover their drawbacks with the other books.Kata Kunci : analisis, buku teks , seni budaya, KTSP